Development of ReaxFFSFOH Force Field for SF6‐H2O/O2 Hybrid System Based on Synergetic Optimization by CMA‐ES and MC Methodology. Issue 19 (6th May 2021) - Liu, Heng; Wang, Jingrui; Li, Qingmin; Haddad, A. Manu
Abstract: The reactive force field (ReaxFF) based molecular dynamic (MD) simulation provides a new perspective for studying the microscopic decomposition mechanism of sulfur hexafluoride (SF6 ) under fault conditions. Since none of the published ReaxFF force fields contains proper interaction relationship between S, F, O and H elements, the development of ReaxFF parameters for SF6 ‐H2 O/O2 hybrid system is urgently needed. In this work, a universal and efficient covariance matrix adaptation evolutionary strategy (CMA‐ES) and Monte‐Carlo FF (MCFF) synergetic (CMS) optimization strategy for ReaxFF parameter is proposed. The optimization results for two representative force fields (disulfide and silica) from literature show that under the same number of evaluations, the CMS optimization strategy significantly reduces the optimization error by 22.08 % (disulfide) and 10.3 % (silica) respectively. By applying CMS strategy, the ReaxFFSFOH force field for SF6 ‐H2 O/O2 hybrid system is efficiently obtained. Through multi‐dimensional force field performance verification, we find that the bond length calculation error between ReaxFF and density functional theory (DFT) calculation results is mainly concentrated within ±0.05 Å, and the bond angle error is mostly within ±5°. In addition, the trends of relative energy changes during chemical reaction processes calculated by ReaxFF are basically consistent with the DFT results. This work lays a solid foundation for the in‐depth study of the microscopic influence mechanism of trace H2 O and trace O2 in the decomposition process of SF6 . Abstract : A novel synergetic optimization strategy (CMS) for ReaxFF parameter optimization is proposed, which can effectively overcome the premature convergence defect of the existing optimization algorithms and significantly improve the optimization effect. By applying this optimization strategy, the ReaxFFSFOH force field of SF6 ‐H2 O/O2 system is obtained, which lays the foundation for studying the decomposition mechanism of SF6 under the fault conditions.